Implementasi Model Pembelajaran Dinamika Kelompok dalam Meningkatkan Motivasi Berprestasi Bidang Non Akademik Anak Berkebutuhan Khusus di SLB YPAC Pangkalpinang - Diah Rina Miftakhi; Maulina Hendrik (Jurnal Pendidikan Kebutuhan Khusus, 2019)
This research is important because it is to determine the level of dissability children’s achievement motivation through the implementation of group dynamics learning models. The purpose of this study is to find out: the implementation of group dynamics learning models to the learning achievement, the process of learning activities carried out using group dynamics learning models, the level of creativity in non-academic fields. The method used in this study is a qualitative descriptive approach with research data sources consisting of: primary data sources and secondary data sources. Techniques for collecting data through observation, interviews, and documentation. The learning model used in YPAC Pangkalpinang SLB is to provide students with practical activities outside the classroom. Learning done were 75% practice and 25% theory. The practice of learning was done by using group dynamics programs with the aim of being able to improve students' non academic achievements. Some of the learning practices include: batik, cooking, makeup, making handicrafts from used materials, and making wedding delivery baskets.